Overlapping Duty of Parents in Distance Learning During Pandemic and Its Impact on Child's Psyche at TK Al-Amanah Campor Barat Ambunten Sumenep - Barratun Naqiyah; Handoko Ja’far (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2021)
This article aims to determine the impact of overlapping parental duties during the pandemic on the psychological condition of children in Distance Learning, based on the results of interviews and observations of students and their guardians at Al-Amanah Campor Barat Kindergarten, Ambunten Sumenep. This article identifies the overlapping duties of parents, namely studying children's school assignments, motivating the children to learn, finding a stable internet network, and providing the monthly internet quotas. Furthermore, the overlapping of parental duties during distance learning has a negative impact on the child's psyche. The indicator is that children feel bored and even cry, because often parents are impatient and yell at them during the implementation of distance learning.